Comorbidity Between Math and Reading Problems: Is Phonological Processing a Mutual Factor? - Amland, Tonje; Lervåg, Arne; Melby-Lervåg, Monica (Frontiers in Human Neuroscience, 2021)
There is a relationship between reading and math skills, as well as a comorbidity between reading and math disorders. A mutual foundation for this comorbidity could be that the quality of phonological representations is important for both early reading and arithmetic. In this study, we examine this hypothesis in a sample traced longitudinally from preschool to first grade (N = 259). The results show that phonological awareness does not explain development in arithmetic, but that there is an indirect effect between phoneme awareness in preschool and arithmetic in first grade via phoneme awareness in first grade. This effect is, however, weak and restricted to verbal arithmetic and not arithmetic fluency. This finding is only partly in line with other studies, and a reason could be that this study more strongly controls for confounders and previous skills than other studies.